Social isolation during COVID-19 x adaptation of society: a data collection : (Research, Society and Development, 2021)
Objective: to verify if social isolation can affect people’s mental health as well as common habits, linked to the idea of being prohibited from leaving home due to the COVID-19 pandemic of the State of Pernambuco / PE. Methodology: This was a cross-sectional and quantitative study with 1.088 individuals, of a non-probabilistic type, for convenience, of both sexes and diferente ages, subjected to the daily changes caused by social isolation, due to the pandemic of the COVID-19 of the State Pernambuco / PE. Results: Most participants were female, with an average of 34,72 years old, reporting that there were no problems related to social isolation, nor Family problems. Most need to adapt to a new reality about hygiene and feelings not felt before the pandemic, stating fear, both of the situation on general and of being infected by COVID-19, as well as social isolation, triggered anxiety and other feelings not experienced before the pandemic. Finally, almost all participants reported believing that dreams will discover na effective treatment for COVID-19. Conclusion: Social isolation as a result of the COVID-19 pandemic can affect both the mental health of individuals, triggering psycho-emotional illnesses and making the process of social adaptation more difficult.